THE EFFECT OF COLLABORATIVE STRATEGY READING ON STUDENTS’ READING COMPREHENSION AT SMA ISLAM TERPADU WAHDAH ISLAMIYAH MAKASSAR - Rindiani; Vivit Rosmayanti; Hasnani (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
This study aims to determine the improvement of students' reading comprehension related to the main idea. Three processes were carried out, namely pretest, treatment and post-test consisting of six meetings. This study is a pre-test and post-test study. The population in this study were students of class X.2 SMA Islam Terpadu Wahdah Islamiyah Makassar and sampling using random sampling technique. The sample in this study was 27 students of class X. The research instrument was a narrative text consisting of 20 multiple-choice questions. The data results showed that there was a difference between students' pre-test and post-test. The main score of students before being given treatment was 42.59 and increased to 62.59 after implementing Collaborative Strategy Reading (CSR). The results of data analysis using the independent T test showed that Sig. (2-tailed) of 0.000 was lower than 0.05 so that (Ha) was accepted and (Ho) was rejected. Based on the results of this study, it can be concluded that Collaborative Strategy Reading can improve the ability to read English texts of tenth grade students of SMA Islam Terpadu Wahdah Islamiyah Makassar